Investigation of the lubrication performance using WC: C coated tool surfaces for hot stamping AA6082. (2017) - Zheng, Kailun; Dong, Yangchun; Dong, Hanshan; Fernandez, Jonathan; Dean, Trevor A
Abstract: This paper presents the lubrication performance of WC: C coated tool surfaces used in hot stamping process of AA6082. A range of cylindrical deep drawing experiments were performed to determine the required minimal lubricant amount under coated and uncoated tooling conditions. In addition, effects of process variables, forming temperature and speed, on the lubrication performance were investigated. The results have shown that the advanced WC: C Diamond-like Carbon (DLC) coating could significantly reduce the use of lubricant for hot stamping. The required amount of lubricant for successful forming decreased with increasing forming speed and decreasing forming temperature. The lubrication mechanisms under different forming conditions were discussed also.